Mitigasi Dampak Banjir dan Rob Terhadap Lahan Pertanian di Kota Pekalongan - Muhammad Wiji Nur Huda Huda; Murtiningrum Murtiningrum; Hanggar Ganara Mawanda; Muhammad Khoiru Zaki; Prieskarinda Lestari; Chandra Setyawan; Bayu Dwi Apri Nugroho; Ngadisih Ngadisih (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
Pekalongan City has an area of 46,42 km2. Based on land use, 19% of the area, which is 886 ha, is agricultural land. The current flood and tidal disasters have an impact on various sectors, including agriculture. Efforts to deal with this problem have been made by the central, provincial and city governments. However, these efforts have not provided a real solution because floods and tidal disasters continue to expand. Therefore, research is needed which aims to identify the impact of flooding and tidal on agricultural land and provide recommendations for mitigating the impacts of flooding and tidal on agricultural land in Pekalongan City. The research was conducted through data collection methods, data quality testing and analysis, disaster mitigation scenarios, and research outputs. Based on the parameters of class III water quality standards, the BOD values at S1, S3, and S6 were 12.5; 27.6; 7.6 mg/L and the COD values at S2, S3, S6 were 53.7; 88.7; 46 mg/L which exceeds/does not meet the requirements. Therefore, it is recommended that good water governance management, water regulation with the mini polder concept, carry out reclamation of affected agricultural land, manufacture of household domestic sewage sanitation channels, and manufacture of purifier ponds.